Histamine and Immune Biomarkers in CNS Disorders. (13th April 2016) - Cacabelos, Ramón; Torrellas, Clara; Fernández-Novoa, Lucía; López-Muñoz, Francisco
Abstract : Neuroimmune dysregulation is a common phenomenon in different forms of central nervous system (CNS) disorders. Cross-links between central and peripheral immune mechanisms appear to be disrupted as reflected by a series of immune markers (CD3, CD4, CD7, HLA-DR, CD25, CD28, and CD56) which show variability in brain disorders such as anxiety, depression, psychosis, stroke, Alzheimer's disease, Parkinson's disease, attention-deficit hyperactivity disorder, migraine, epilepsy, vascular dementia, mental retardation, cerebrovascular encephalopathy, multiple sclerosis, brain tumors, cranial nerve neuropathies, mental retardation, and posttraumatic brain injury. Histamine (HA) is a pleiotropic monoamine involved in several neurophysiological functions, neuroimmune regulation, and CNS pathogenesis. Changes in brain HA show an age- and sex-related pattern, and alterations in brain HA levels are present in different CNS regions of patients with Alzheimer's disease (AD). Brain HA in neuronal and nonneuronal compartments plays a dual role (neurotrophic versus neurotoxic) in a tissue-specific manner. Pathogenic mechanisms associated with neuroimmune dysregulation in AD involve HA, interleukin-1 β, and TNF- α, whose aberrant expression contributes to neuroinflammation as an aggravating factor for neurodegeneration and premature neuronal death.